Temozolomide and 13-cis retinoic acid in patients with anaplastic gliomas: a prospective single-arm monocentric phase-II study (RNOP-05) - Grauer, Oliver Martin; Pascher, Christina; Hartmann, Christian; Zeman, Florian; Weller, Michael; Proescholdt, Martin; Brawanski, Alexander; Pietsch, Thorsten; Wick, Wolfgang; Bogdahn, Ulrich; Hau, Peter (Journal of neuro-oncology, 2011)
The objective of this prospective, monocentric phase-II pilot study was to evaluate toxicity and efficacy of neoadjuvant temozolomide (TMZ) and 13-cis retinoic acid (13-cRA) treatment in patients with newly diagnosed anaplastic gliomas after total or subtotal tumor resection. The primary endpoint of the study was median progression-free survival (PFS). Secondary endpoints were toxicity and PFS rates at 6, 12 and 24 months. Thirty-two adult patients were included in the study and treated with a median number of 10 TMZ and 13-cRA cycles (range 1-26). The majority of patients had favorable prognostic factors characterized by young age, complete resection, oligodendroglial histology, 1p/19q co-deletion, O6-methylguanine-DNA methyltransferase (MGMT) promotor methylation and isocitrate dehydrogenase 1 (IDH1) mutation. Grade 3/4 myelotoxicity occurred in 5/32 patients, and about 90% of patients suffered from grade 2/3 adverse events attributable to 13-cRA. The median PFS was 37.8 months (95% CI 22.2-53.4). The 6-, 12- and 24-month PFS rates were 84.4, 75 and 42.4%. The extent of tumor resection was the only prognostic factor associated with better PFS. TMZ and 13-cRA treatment did not improve PFS when retrospectively compared to the TMZ-treated group within the randomized NOA-04 phase-III trial. In conclusion, 13-cRA addition to TMZ in a neoadjuvant setting showed acceptable toxicity, but did not yield an advantage in PFS in patients with newly diagnosed anaplastic gliomas after total or subtotal tumor resection.
Gesehen am 11.07.2022